Pulsed Electric Field Equipment for Electropastaurization of Dairy Products (London Journal of Engineering Research, 2024)
More than 549 million metric tons of cow's milk were produced in the world in 2023, and the production volume of cheese and butter exceeded 22 million tons, respectively. This is why food security in this sector is crucial.To ensure that production is of high quality, Brazilian researchers developed industrial pasteurizing equipment that works with electrical fields. The invention is protected under patent WO2018090110 - system and method for neutralizing pesticides or similar agents contained in food and constructive configuration for its implementation.Consumers are showing interest in preservation technologies that do not rely on heating. The effect of the device on the elimination of pathogens in dairy products is investigated.